MANAJEMEN LAYANAN BIMBINGAN KONSELING DALAM MEMBANTU ADAPTASI SISWA LULUSAN SMP DI MAN - M. Robert Farmadi; Adi Wibowo; Isnaini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Differences in curriculum characteristics between Junior High Schools (SMP) and State Islamic Senior High Schools (Madrasah Aliyah Negeri/MAN) create academic and socio-cultural adaptation challenges for SMP graduates entering madrasah education. These challenges are not merely related to students’ individual readiness but also reflect institutional limitations in managing curriculum transition within Islamic educational settings. This study aims to analyze adaptation difficulties experienced by SMP graduates, examine the role of guidance and counseling (GC) service management as part of transition management, and identify structural constraints affecting the effectiveness of GC services in MAN Purworejo. This study employs a qualitative case study approach. Data were collected through in-depth interviews, observation, and documentation, and analyzed using interactive data analysis techniques. The findings indicate a significant curriculum gap between SMP and MAN that affects students’ academic readiness and socio-religious adaptation. GC services have contributed to student adjustment; however, their implementation remains largely reactive and has not been fully integrated into institutional transition management. This study emphasizes the importance of strengthening GC service management within Islamic education institutions to address curriculum transition and student adaptation more systematically.